Rainfall prediction system with predictors of temperature humidity, wind speed and air temperature using r programming language - Anita Sari; Susanto; Harma Oktafia Lingga Wijaya Wijaya (International Journal Cister, 2023)
Rainfall is a climatic factor that can affect human survival, especially in the agricultural sector. Lubuklinggau City is one of the agricultural areas in the province of South Sumatra. Information about rainfall is needed by farmers in Lubuklinggau City. In determining planting time, generally farmers in the city of Lubuklinggau are only based on observing conditions, without looking at information about climate or rainfall. This is caused by the lack of information about rainfall provided by the government. A prediction system is a system that can process or estimate systematically about something that is most likely to happen in the future based on past and present information that is owned, so that the error (the difference between something that happened and the estimated result) can be minimized. Generally in a prediction system there is a calculation method used. One method that is often used in prediction systems is multiple linear regression. Multiple linear regression analysis was carried out to determine the direction and how much influence the independent variables have on the dependent variable. From the research results, the test values obtained were MSE (Mean Squere Error) = 0.8206, RMSE (Root Mean Squere Error) = 0.9059 and MAPE (Mean Absolute Percentage Error) = 39.886. Based on the calculation results mape value is equal to 39.886.